ANATEKS: An eContent learning for 'Technical Analysis' - Nor, Amirudin Mohd; Jantan, Mohd Jefary; Abu Zarin, Noor Adriana; Ahmad Marzuki, Izzah Nabihah; Halim, Nurrabiatul Adawiyah (2020)
‘Technical analysis’, a branch of stock market study is a popular and heavily used technique in stock trading. Few knowledge and educational materials have been produced to assist beginners in this industry. The present learning tools, named ANATEKS, a short form for ‘Asas Analisis Teknikal Saham’ was developed as an eContent educational platform catering for the first-time learners in technical analysis. The platform provides introductory information on the subjects in a compact duration via short videos. Using smartphones and computers, the materials are accessible through ANATEKS website linked to youtube. Such medium complements the existing conventional learning via lectures and book reading. It helps to boost learning experience in a convenient, timeless, fun and fast way. The potential target includes the students of Universiti Teknologi MARA (UiTM) Melaka enrolled in the technical analysis course and the general public who is the first timer in Bursa Malaysia trading. Uniquely, the videos are prepared by beginners in this area, suiting the tagline ‘learning from peers.” Guided by SCANMIC methodology in producing a successful eContent learning method by Hassan & Li [1], overall ANATEKS fulfil majority of the SCANMIC paradigm features making it a useful learning medium for new investors. Future recommendation includes the inclusion of industry experts learning materials in the form of videos and pdf documents, coupled with knowledge sharing interactive features in the website.